The global joint distribution of income and health - Ximing Wu; Andreas Savvides; Thanasis Stengos (Center for Economic Studies and ifo Institute (CESifo), 2008)
We investigate the evolution of global welfare in two dimensions: income per capita and life expectancy. First, we estimate the marginal distributions of income and life expectancy separately. More importantly, in contrast to previous univariate approaches, we consider income and life expectancy jointly and estimate their bivariate global distribution for 137 countries during 1970 - 2000. We reach several conclusions: the global joint distribution has evolved from a bimodal into a unimodal one, the evolution of the health distribution has preceded that of income, global inequality and poverty has decreased over time and the evolution of the global distribution has been welfare improving. Our decomposition of overall welfare indicates that global inequality would be underestimated if within-country inequality is not taken into account. Moreover, global inequality and poverty would be substantially underestimated if the dependence between the income and health distributions is ignored.
Keywords: O1; O15; O57; 330; Income; health; global distribution; inequality; poverty; Einkommensverteilung; Gesundheit; Sozialprodukt; Sterblichkeit; Wohlfahrtseffekt; Welt